Quercetin Suppresses AOM/DSS-Induced Colon Carcinogenesis through Its Anti-Inflammation Effects in Mice. (21st May 2020) - Lin, Rui; Piao, Meiyu; Song, Yan; Liu, Chunyan
Abstract : Colorectal cancer (CRC) is the fourth leading cause of tumor-related deaths worldwide. In this study, we explored the in vivo effects of quercetin, a plant flavonol from the flavonoid group of polyphenols with antioxidant effects, on colon carcinogenesis induced by azoxymethane/dextran sodium sulfate (AOM/DSS). Thirty mice were randomly assigned into three groups: the control group, the AOM/DSS group, and the quercetin+AOM/DSS group. CRC was induced by AOM injection and a solution of 2% DSS in the drinking water. In the AOM/DSS-induced colon cancer mice model, quercetin treatment dramatically reduced the number and size of colon tumors. In addition, quercetin significantly restored the leukocyte counts by decreasing the inflammation caused by AOM/DSS. We also observed that the expression of oxidative stress markers, such as lipid peroxide (LPO), nitric oxide (NO), superoxide dismutase (SOD), glucose-6-phosphate (G6PD), and glutathione (GSH), could be reduced by quercetin, suggesting that the anti-inflammatory function of quercetin comes from its antioxidant effect. Moreover, potential biomarkers were identified with serum metabolite profiling. Increased levels of 2-hydroxybutyrate, 2-aminobutyrate, and 2-oxobutyrate and decreased levels of gentian violet, indole-3-methyl acetate, N-acetyl-5-hydroxytryptamine, indoxyl sulfate, and indoxyl were also found in the AOM/DSS-treated mice. However, quercetin treatment successfully decreased the levels of 2-hydroxybutyrate, 2-aminobutyrate, 2-oxobutyrate, endocannabinoids, and sphinganine and increased the levels of gentian violet, N-acetyl-5-hydroxytryptamine, indoxyl sulfate, and indoxyl. Together, our data demonstrated that quercetin could maintain relatively potent antitumor activities against colorectal cancer in vivo through its anti-inflammation effect.